Health state of the population in Poland and Ukraine and its conditioning in the period of transformation. - Pantylej, Wiktoria (Bulletin of Geography. Socio-economic Series, 2007)
The main aim of the article was the evaluation of the directions, scale and influence of socio-economic reforms implemented during 1990-2002 on the population's state of health in Ukraine and in Poland. The author of the article attempts to select and determine partial and synthetic indices and factors influencing public health. The article presents the typology of provinces in Ukraine and voivodeships in Poland which was developed with regard to the health status of the population and its influencing factors. Socio-economic reforms conducted in Ukraine have caused drastic deterioration of people's health while in Poland one can observe the improvement in a number of indices characterising the health of the population and socio-economic situation of the country.